The Influence of Tax Planning and Tax Avoidance on Firm Value (Evidence from the Manufacturing Sector in Indonesia) - Sari, Alsi Nurmala; Mahwiyah, Mahwiyah; Maulana, Ingga (Jurnal Multidisiplin Sahombu, 2025)
This study examines the influence of tax planning and tax avoidance on firm value in the manufacturing sector listed on the Indonesia Stock Exchange during a multi-year period. The purpose of this research is to assess whether strategic tax behavior contributes positively or negatively to the perceived value of a firm. The data used were obtained from audited financial statements and market price records, analyzed using panel data regression with the fixed effect model. The findings reveal that tax planning has a significant positive impact on firm value, indicating that efficient and legal tax strategies enhance investor confidence and corporate performance. On the other hand, tax avoidance shows no significant effect on firm value, suggesting that aggressive tax minimization efforts may not necessarily contribute to long-term shareholder value. These results support the agency theory, which emphasizes the alignment of management actions with shareholder interests. The study provides implications for corporate governance and tax policy compliance.